A literature survey on follow-up definitions on the use of infliximab in Crohn’s disease - Andy Wai Kan Yeung (Therapeutic Advances in Gastroenterology)
Many clinical studies arbitrarily define follow-up durations as short-term, mid-term, or long-term, without standardized criteria. To examine existing research on the use of infliximab in Crohn’s disease to understand how these terms are defined and applied, a literature survey was conducted. Relevant studies were identified by querying Web of Science and Scopus with predefined keywords, focusing on articles that mentioned “short-term,” “mid-term,” or “long-term” in their title, abstract, or author keywords. The majority of the papers were published in gastroenterology and hepatology journals (75.6%), since 2010 (77.3%), and primarily involved retrospective data (64.8%). Most studies measured follow-up duration from the first infliximab infusion (65.3%). The mean follow-up durations were 4.06 months for short-term (based on 46 papers), 9.47 months for mid-term (based on 3 papers), and 37.58 months for long-term studies (based on 155 papers). Retrospective studies tended to have significantly longer mean durations for long-term follow-up than prospective studies. Notably, the ranges for short-term and long-term follow-ups overlapped, indicating inconsistent definitions across studies. Currently, there is no consensus on the durations associated with these terms. Standardized reporting with explicit timeframes in months or years is essential to improve comparability and clarity in future research.